Temporal and spatial variation in polychlorinated biphenyl chiral signatures of the Greenland shark (Somniosus microcephalus) and its arctic marine food web - Lu, Zhe; Fisk, Aaron T.; Kovacs, Kit M.; Lydersen, Christian; McKinney, Melissa A.; Tomy, Gregg T.; Rosenburg, Bruno; McMeans, Bailey C.; Muir, Derek C.G.; Wong, Charles S. (Environmental Pollution, 2014)
Polychlorinated biphenyls (PCBs) chiral signatures were measured in Greenland sharks (Somniosus microcephalus) and their potential prey in arctic marine food webs from Canada (Cumberland Sound) and Europe (Svalbard) to assess temporal and spatial variation in PCB contamination at the stereoisomer level. Marine mammals had species-specific enantiomer fractions (EFs), likely due to a combination of in vivo biotransformation and direct trophic transfer. Greenland sharks from Cumberland Sound in 2007-2008 had similar EFs to those sharks collected a decade ago in the same location (PCBs 91, 136 and 149) and also similar to their conspecifics from Svalbard for some PCB congeners (PCBs 95, 136 and 149). However, other PCB EFs in the sharks varied temporally (PCB 91) or spatially (PCB 95), suggesting a possible spatiotemporal variation in their diets, since biotransformation capacity was unlikely to have varied within this species from region to region or over the time frame studied. © 2013 Elsevier Ltd. All rights reserved.